(Re)imagining intelligent journalism - López-García, Xosé (Anuario ThinkEPI, 2024)
The emergence of the impact of Artificial Intelligence (AI) in technologically mediated communicative processes has not only opened new debates in journalism but has also put on the table, once again, its future in a network society where, despite ubiquity, truthful information circulating through different channels and in all types of formats represents a small part of the communicative flows. After the long shadows of the turbulences that have accompanied journalism in the first waves of digital transformation, the irruption of AI in newsrooms announces new opportunities and poses renewed threats, in a context of regulation and expectation about the ability to order the new scenario in favor of citizens. An analytical review of the contributions and fears raised by the new challenges animates the design of some elements that drive initiatives that seek to imagine intelligent journalism. Given that machines do not have firm commitments to truth and honesty, nor do they have all the coordinates that point them to the discipline of verification as the essence of journalism, we bet on hybrid artificial intelligence, which combines different algorithms and machine learning techniques with human knowledge and logic, as one of the best ways to achieve a more intelligent journalism -total journalism that takes advantage of all the techniques and modalities inherited from the past.
Keywords: Artificial intelligence; Hybrid intelligence; Digital journalism; Total journalism